Process of Analyzing Choice of Law Problems - Charles D. Kelso (Washington University Law Quarterly, 1959)
Just as lawyers develop mental check lists for typical matters of significance in personal injury cases, divorces, wills, etc., so should they prepare to spot the most important choice of law problems. This project deserves high priority in any lawyer's list of "should do's" since the check list could be used in almost every case. One purpose of this Article is to suggest its major components.
Keywords: Conflict of laws